2019
DOI: 10.1021/acs.langmuir.9b03394
|View full text |Cite
|
Sign up to set email alerts
|

Closest-Packing Water Monolayer Stably Intercalated in Phyllosilicate Minerals under High Pressure

Abstract: The directional hydrogen-bond (HB) network and nondirectional van der Waals (vdW) interactions make up the specificity of water. Directional HBs could construct an ice-like monolayer in hydrophobic confinement even in the ambient regime. Here, we report a water monolayer dominated by vdW interactions confined in a phyllosilicate interlayer under high pressure. Surprisingly, it was in a thermodynamically stable state coupled with bulk water at the same pressure (P) and temperature (T), as revealed by the thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…The basic layers of Mnt and Ilt models were based on the structure of pyrophyllite . These structures have been reliably verified in other simulation studies. …”
Section: Models and Simulation Detailssupporting
confidence: 69%
“…The basic layers of Mnt and Ilt models were based on the structure of pyrophyllite . These structures have been reliably verified in other simulation studies. …”
Section: Models and Simulation Detailssupporting
confidence: 69%
“…Nevertheless, they reveal that for a crystalline interface that does not form hydrogen bonds well, pressure‐induced water intercalation is anticipated. Pressure‐induced water intercalation has also been observed in talc and kaolinite interlayers (Chen, Zhou, Zhu, Lu, & He, 2020; Chinnery et al., 1999; Fumagalli et al., 2001; Hwang et al., 2017). Our previous simulation study of talc and kaolinite with multiple crystalline layers stacking under a periodic boundary condition showed that water can be intercalated when pressure is high (Chen, Zhou, Zhu, Lu, & He, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Hydroxyl groups on the talc surface with Si vacancies, were thought to be the reason for interlayer hydration, as the increased hydrophilicity with the addition of hydroxyl groups was intuitively thought to favor water intercalation. However, our previous study showed that Si vacancies are not necessary for interlayer hydration (Chen, Zhou, Zhu, Lu, & He, 2020). A crystalline interface with hydrophobic surfaces favors water intercalation at high pressure, which, although counterintuitive, can be justified by the volume‐loss effect.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…μ i and μ f at certain temperature and pressure conditions are derived with TI through decoupling interactions between a water molecule and surrounding environment, which can be found in our previous studies (Chen et al 2020a;Chen et al 2020b;Zhou et al 2020) and briefly introduced in Section S2 of the Supplemental Material.…”
Section: Determination Of Stable Hydration State Of Smectitementioning
confidence: 99%